Research on Herb Pairs of Classical Formulae of ZHANG Zhong-Jing Using Big Data Technology - Huang Xin-Di; Ding Chang-Song; Liang Hao; Xiong Shi-Wei; Li Li-Song (KeAi Communications Co., Ltd., 2019)
Objective: To analyze various herbal combinations in Treatise on Exogenous Febrile Diseases (Shang Han Lun,《伤寒论》) and Synopsis of Prescriptions of the Golden Chamber (Jin Gui Yao Lve, 《金匮要略》), seeking to identify fundamental rules dictating the selection of herbal combinations through probability models and big data technology. Methods: A total of 252 formulae were collected from Treatise on Exogenous Febrile Diseases (Shang Han Lun, 《伤寒论》) and Synopsis of Prescriptions of the Golden Chamber (Jin Gui Yao Lve, 《金匮要略》) by ZHANG Zhong-Jing. Formulae were then preprocessed with all herb names standardized. The concepts of candidate herb pair and candidate herb pair probability were proposed to analyze the rules of combinations in classical formulae based on probability statistics. MapReduce parallel computing framework of distributed big data technology was adopted to analyze large data samples combined with inverted index algorithm. Results: The results showed that the core herbs were Glycyrrhizae Radix Rhizoma (Gan Cao, 甘 草 ), Cinnamomi Ramulus (Gui Zhi, 桂 枝 ), Zingiberis Rhizoma Recens (Sheng Jiang, 生姜), Jujubae Fructus (Da Zao, 大枣), Paeoniae Radix Alba (Bai Shao, 白 芍 ), etc. 43 high-frequency pairs co-occurring 10 times or above were extracted, and 35 of these combinations were recognized as traditional herb pairs, such as Cinnamomi Ramulus (Gui Zhi, 桂枝) - Glycyrrhizae Radix Rhizoma (Gan Cao, 甘草), Zingiberis Rhizoma Recens (Sheng Jiang, 生姜) - Jujubae Fructus (Da Zao, 大枣), and Cinnamomi Ramulus (Gui Zhi, 桂枝) - Ginseng Radix Et Rhizoma (Ren Shen, 人参). The other 8 pairs of combinations, such as Paeoniae Radix Alba (Bai Shao, 白芍) - Zingiberis Rhizoma Recens (Sheng Jiang, 生姜), Paeoniae Radix Alba (Bai Shao, 白 芍 ) - Jujubae Fructus (Da Zao, 大 枣 ), and Zingiberis Rhizoma Recens (Sheng Jiang, 生姜) - Ginseng Radix Et Rhizoma (Ren Shen, 人参), were not defined traditionally, but in connection with commonly used herbs. Classical formulae took the core herbs as principles, focusing on tonifying deficiency, strengthening the spleen and the stomach, strengthening the healthy Qi, and eliminating pathogenic factors. The compatibility pattern of properties involved was mainly acrid and sweet, which reflected the compatibility laws of benefiting Qi and tonifying Yang, replenishing Qi and nourishing blood, etc. Conclusions: The research of classical formulae provides common understanding of some basic rules that have been adopted to tackle common illnesses/diseases using herbal medicine. The results help to reinforce theoretical understanding and development of traditional Chinese medicine (TCM), and revealing the hidden rules of combination in TCM data. Analyzing wider data samples of various herbal combinations through computation and big data technology can further optimize the use of TCM. Keywords: Classic formulae, Herb pair, Herbal medicine, Big data, TCM compatibility rules